Promosi Pertumbuhan Sapi Bali pada Penggemukan Pakan Kurung dengan Addisi Ionophore-Polyether Dalam Ransum - Lalu Wira Pribadi (Jurnal Ilmu Dan Teknologi Peternakan Indonesia (JITPI) Indonesian Journal of Animal Science and Technology), 2015)
The optimum level of using Ionophore-polyether (Salinomycin) to promote Bali cattle growth has been investigated by treating dietary containing 0; 50; 100; and 150 mg Salinomycin to 40 heads of uniformly Bali cattle. Variables measured were feed consumption, growth rate, and fattening efficiency. Data were analysed by using Analysis of Variance and further test by using Duncanâ€™s New Multiple Range Test. The optimum level of using Ionophore-polyether (Salinomycin) was determined by a treatement showing the highest fattening efficiency values. Results of the experiment showed that adding Salinomycin in diet for male Bali cattle fattening promote 19,2% daily gain. Adding the Salinomycin in basal diet which consisted of 83,0% natural grasses and 13,0% rice bran, were â€œoptimumâ€ at the level of 100,0 mg/head/day on both growth rate and fattening efficiency of male Bali cattle.